Performance Analysis of BLoC and GetX State Management Library on Flutter - Zulistiyan, Mohamad; Adrian, Monterico; Wibowo, Yanuar Firdaus Arie (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research delves into evaluating Flutter's BLoC and GetX state management libraries, focusing on their memory and CPU usage across diverse dataset sizes of 1,000, 5,000, and 10,000 entries. The objective is to identify which library offers better performance efficiency in Flutter application development. Addressing the critical problem of resource optimization, the study uses a comparative analytical approach. Preliminary results indicate GetX's higher memory efficiency with smaller datasets and BLoC's superior CPU efficiency in handling larger datasets. These findings are pivotal for developers in choosing the right library, aligning with the specific performance demands and scalability needs of their applications, thereby ensuring enhanced functionality and user experience. This contributes significantly to the understanding of state management's impact on Flutter app performance, offering a detailed guide for optimal library selection in the ecosystem.